Non Binary Options in Gender Choice (Perspective on Human Rights and Islamic Religion) - Indra Kertati*; Desi Asmaret; Fadil Mas’ud; Muhammad Dheo Adrian Muhari; Nety Novita Hariyani (Riwayat: Educational Journal of History and Humanities, 2023)
Abstract: The Human Rights perspective and the Islamic perspective have quite significant differences in viewing non-binary options in gender choices. This research aims to specifically compare these two perspectives. This research is qualitative research with a comparative descriptive approach regarding human rights and Islamic views on non-binary options in gender choices. The data used in this research is secondary data. The data collection technique in this research uses the library research method. The analysis technique in this research uses analytical techniques for data collection, data selection, data reduction, and drawing conclusions. The results of this research show that from a human rights perspective there is no problem with the inclusion of non-binary options in gender choices. This is in line with the fundamental principles contained in human rights, namely regarding sexuality rights which include the right to privacy, the right to autonomy over oneself, and human rights. This is in contrast to the Islamic perspective which views human gender from a biological aspect as consisting of only two groups, namely men and women. Each group has its own limitations in carrying out worship and muamalah. Even if physically there are humans who are born with two genders. So you are required to choose the most dominant of the two things.  Abstrak: Perspektif Hak Asasi Manusia dan perspektif Islam memiliki perbedaan yang cukup signifikan dalam memandang opsi non biner dalam pilihan gender. Penelitian ini bertujuan mengkomparassi secara seskriftif dua perspektif tersebut. Penelitian ini merupakan penelitian kualitatif dengan pendekatan desriftif komparatif mengenai pandangan Hak Asasi Manusia dan Islam terhadap opsi non biner dalam pilihan gender. Data yang digunakan dalam penelitian ini merupakan data sekunder. Teknik pengumpulan data dalam penelitian ini menggunakan metode pustaka/library research. Teknik analisis dalam peneltian ini menggunakan teknik analisis pengumpulan data, seleksi data, reduksi data, dan penarikan kesimpulan. Hasil penelitan ini menunjukkan, dalam perspktif Hak Assasi Manusia tidak mempermasalahkan masuknya opsi non biner dalam pilihan gender hal tersebut sejalan dengan prinsip-prinsip fundamental yang ada dalam Hak Asasi Manusi yakni mengenai sexuality right yang meliputi hak atas privasi, hak otonom atas diri sendiri, dan hak asasi manusia. Berbanding trebalik dalam perspektif Islam yang memandang gender manusia dari aspek bilogis hanya terdiri darri dua golongan yakni laki-laki dan perempuan. Setiap golongan memiliki batasan masiing-masing dalam melaksanakan ibadah dan muamalah. Bahkan apabila secara fisik terdapat manusia yang terlahir dengan dua jenis kelamin. Maka diharuskan memilih salah satu yang paling dominan dari du hal tersebut.